Living benthic foraminifera from El Ferrol Bay: A pollution critical area in northern-central Peru - Romero, Dennis (2023)
The study focused on the assemblage of ‘living’ benthic foraminifera (stained with Rose Bengal) in the surface sediments of El Ferrol Bay (Chimbote, 9°S). Twelve sampling sites were selected at depths ranging from 4.5 to 27 meters in September 2015. Water samples were collected near the seafloor to determine dissolved oxygen (DO), pH, and nutrient (nitrate and phosphate). Sediment samples were analysed for total organic matter (TOM) and the chlorophyll-a to phaeopigment ratio (chl-a/phaeo. Our findings confirm that this bay experiences hypoxic conditions at the seafloor (~2 mL/L) in addition to high dissolved nitrate levels. The assemblage was primarily composed of hyaline calcareous species, a porcelaneous calcareous species, and a soft-shelled foraminiferal species. Densities ranged from moderate to high, with the calcareous species Bolivina costata being the dominant species and B. elegantissima co-dominant in most sites. Based on our analysis, no significant differences were observed between the assemblages of living benthic foraminifera in the inner and outer bay. However, the influence of bottom nitrates on shallow-water foraminiferal species was notable. These results provide a baseline reference for future monitoring and calibration studies.